2013
DOI: 10.1515/ijamh-2013-0007
|View full text |Cite
|
Sign up to set email alerts
|

Development of adiposity, obesity and age at menarche: an 8-year follow-up study in Portuguese schoolgirls

Abstract: EM seems to be a risk factor for the development of obesity during adolescence. However, this vulnerability may start to be programmed before menarche as girls with precocious menarche were already fatter than their late-maturing peers at age 7 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 43 publications
(55 reference statements)
1
12
2
1
Order By: Relevance
“…The relationship of BMI with earlier puberty has also been observed in some European populations: in Swedish children, a negative correlation was observed between the change in BMI between the ages of 2 to 8 and the age of the peak height velocity, considered a puberty marker . In addition, Portuguese school girls that were obese from 7 years old had earlier menarche than their normal‐weight counterparts . Therefore, controlling weight gain between pre‐pubertal school age and adolescence may aid in the prevention of comorbidities associated with earlier puberty.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The relationship of BMI with earlier puberty has also been observed in some European populations: in Swedish children, a negative correlation was observed between the change in BMI between the ages of 2 to 8 and the age of the peak height velocity, considered a puberty marker . In addition, Portuguese school girls that were obese from 7 years old had earlier menarche than their normal‐weight counterparts . Therefore, controlling weight gain between pre‐pubertal school age and adolescence may aid in the prevention of comorbidities associated with earlier puberty.…”
Section: Discussionmentioning
confidence: 78%
“…Therefore, longitudinal studies are needed to evaluate the directionality of the relationship between body composition and puberty and to study this influence. There are several longitudinal PEDIATRICOBESITY ORIGINALRESEARCH doi:10.1111/ijpo.277 studies that have found a relationship between pubertal development and pre-pubertal anthropometric variables (mainly BMI) even as early as pre-school age (19)(20)(21)(22)(23). Nevertheless, the relationship between anthropometric variables at birth and age of pubertal development remains unclear (17,21,24).…”
Section: Introductionmentioning
confidence: 99%
“…Childhood obesity could influence development of endometrial cancer in several ways. It may result in earlier menarche, which increases the risk of endometrial cancer . Childhood obesity may reduce levels of sex‐hormone binding globulin, which increases levels of non‐SHBG‐bound estrogen .…”
mentioning
confidence: 99%
“…Furthermore, many studies demonstrate that increased adiposity is associated with earlier onset of menarche 46 . An older age of menarche is observed in populations with a lower rate of literacy, and Thomas et al suggest that this is due to the physical activity associated with child labor 2 .…”
Section: Introductionmentioning
confidence: 99%